Influencer Marketing Model of Purchase Decisions With Customer Engagement As a Mediation Variable - Natasya Dara Irdiyanti; Riris Roisah; Ani Solihat; Djunarto; Andry Trijumansyah (UPI YPTK Journal of Business and Economics, 2026)
This study aims to determine the influence of influencer marketing on purchase decisions with customer engagement as a mediating variable in RDA Hijab consumers on the TikTok platform. This study uses a survey method with a quantitative approach and involves 130 respondents. The data analysis technique uses SmartPLS. The results of the study show that there is a significant influence between influencer marketing on purchase decisions. Customer engagement also has a significant effect on purchasing decisions. In addition, influencer marketing has been proven to have a significant indirect influence on purchase decisions through customer engagement. This proves that customer engagement plays a significant role in the relationship and is included in the category of complementary mediation. These findings confirm that the effectiveness of influencer marketing strategies will be more optimal if they are able to build consumers' emotional engagement with brands.